The Value-relevance of Non-financial Information in Pharmaceutical Industry in China. - Cheng, Sijia (2017)
This study examines whether non-financial information is useful to investors in assessing and valuing pharmaceutical firm’s long-term financial performance. Earnings per share and book value are generally considered to be the most important indicators of operations in traditional industries. However, financial information is no longer as important as it used to be when it comes to evaluating the financial performance in pharmaceuticalindustries. In this paper, rate of technical staff and cumulative patent count in a firm are the main non-financial information to value the share price of pharmaceutical companies. And this paper also draw several conclusions about the non-financial information impact on share price and firm value in pharmaceutical industries.